Variations in the lipid peroxidation and antioxidant biomarkers in some tissues of anadromous cyprinid fish during migration - Kaptaner, Burak; Dogan, Abdulahad (Cellular and Molecular Biology, 2019)
Alburnus tarichi is an endemic fish species inhabiting the Lake Van basin of Turkey. This anadromous cyprinid fish migrates for spawning to the freshwater inlets pouring into Lake Van, which has highly alkaline and brackish water. During the migration, the fish moves to a new habitat from a different habitat and encounters many challenges. The objective of the present study is to investigate whether antioxidant responses occur in the tissues of A. tarichi during its anadromous migration. To this end, fish were sampled at three different points and in two different periods from the migration route, including in Lake Van at prespawning, at the entrance of a freshwater stream (Karasu) at spawning and in the upstream of the freshwater stream at spawning. Malondialdehyde (MDA) content and antioxidant defenses including activities of the enzymes superoxide dismutase, glutathione peroxidase, glutathione-S-transferase and catalase and the level of glutathione were assayed in liver, gill, white muscle, trunk kidney and anterior intestine tissues. Our results showed increased MDA levels in liver, white muscle and anterior intestine and tissue-specific antioxidant responses in the freshwater environment. This study reports that alterations occurred in the antioxidant defense system indicators in the tissues of anadromous cyprinid fish during migration and that the antioxidant defenses might reflect an important role in spawning migration that ultimately leads to accomplishment of reproductive activity.